an analysis of one young boy acquisition of Kupang malay as a second language - Sene, Chamelya Vivi Crystanty (LP3MKIL, 2022)
This research article is aimed at knowing how much Kupang Malay this one boy has acquired after living in Kupang. To answer the question mentioned above, the writer used the descriptive method, the subject of this research was one young boy who came to Kupang to continue his study and can not speak Kupang Malay at all. In collecting the data, the writer took the recording and The result of the analysis shows that he is good at acquiring Kupang Malay. Keywords: Acquiring, Kupang, Malay.